calc lab 2

# calc lab 2 - 0 1 5-6 15 3-8 1 0 53>> B(4)=B(4-3*B(1 B =...

This preview shows pages 1–5. Sign up to view the full content.

LAB 2-Brad Finley >> B=[2 -1 4 -5 27; -1 3 -2 -1 -26; 0 1 5 -6 15; 3 -8 1 0 53] B = 2 -1 4 -5 27 -1 3 -2 -1 -26 0 1 5 -6 15 3 -8 1 0 53 >> B(2,:)=B(2,:)+B(1,:) B = 2 -1 4 -5 27 1 2 2 -6 1 0 1 5 -6 15 3 -8 1 0 53 >> B(2,:)=B(2,:)-(1/2)*B(1,:) B = 2 -1 4 -5 27 0 5/2 0 -7/2 -25/2 0 1 5 -6 15 3 -8 1 0 53 >> B(1,:)=2*B(1,:)-B(4,:) B = 1 6 7 -10 1 0 5/2 0 -7/2 -25/2

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 0 1 5 -6 15 3 -8 1 0 53 >> B(4,:)=B(4,:)-3*B(1,:) B = 1 6 7 -10 1 0 5/2 0 -7/2 -25/2 0 1 5 -6 15 0 -26 -20 30 50 >> B(4,:)=B(4,:)+26*B(3,:) B = 1 6 7 -10 1 0 5/2 0 -7/2 -25/2 0 1 5 -6 15 0 0 110 -126 440 >> B(3,:)=5*B(3,:)-2*B(2,:) B = 1 6 7 -10 1 0 5/2 0 -7/2 -25/2 0 0 25 -23 100 0 0 110 -126 440 >> B(4,:)=B(4,:)-4.4*B(3,:) B = 1 6 7 -10 1 0 5/2 0 -7/2 -25/2 0 0 25 -23 100 0 0 * -124/5 * >> A=[-2 1 9 1; 3 3 -4 2; 1 4 5 5] A =-2 1 9 1 3 3 -4 2 1 4 5 5 >> A(3,:)=2*A(3,:)+A(1,:) A =-2 1 9 1 3 3 -4 2 0 9 19 11 >> A(1,:)=A(1,:)+A(2,:) A = 1 4 5 3 3 3 -4 2 0 9 19 11 >> A(2,:)=A(2,:)-3*A(1,:) A = 1 4 5 3 0 -9 -19 -7 0 9 19 11 >> A(3,:)=A(3,:)+A(2,:) A = 1 4 5 3 0 -9 -19 -7 0 0 0 4 >> a=[2 3 -4 1 2; 3 -1 -1 2 4; 1 -7 5 -1 6;0 0 0 0 0] a = 2 3 -4 1 2 3 -1 -1 2 4 1 -7 5 -1 6 0 0 0 0 0 >> a(1,:)=a(1,:)-a(3,:) a = 1 10 -9 2 -4 3 -1 -1 2 4 1 -7 5 -1 6 0 0 0 0 0 >> a(2,:)=a(2,:)-3*a(3,:) a = 1 10 -9 2 -4 0 20 -16 5 -14 1 -7 5 -1 6 0 0 0 0 0 >> a(3,:)=a(3,:)-a(1,:) a = 1 10 -9 2 -4 0 20 -16 5 -14 0 -17 14 -3 10 0 0 0 0 0 >> a(3,:)=20*a(3,:)+17*a(2,:) a = 1 10 -9 2 -4 0 20 -16 5 -14 0 0 8 25 -38 0 0 0 0 0 >> b=[2 3 -4 4; 8 11 -7 8;2 2 -4 -3] b = 2 3 -4 4 8 11 -7 8 2 2 -4 -3 >> b(2,:)=b(2,:)-4*b(1,:) b = 2 3 -4 4 0 -1 9 -8 2 2 -4 -3 >> b(1,:)=1.5*b(1,:)-b(3,:) b = 1 5/2 -2 9 0 -1 9 -8 2 2 -4 -3 b = 1 5/2 -2 9 0 -1 9 -8 2 2 -4 -3 >> b(3,:)=b(3,:)-2*b(1,:) b = 1 5/2 -2 9 0 -1 9 -8 0 -3 0 -21 >> b(3,:)=b(3,:)-3*b(2,:) b = 1 5/2 -2 9 0 -1 9 -8 0 0 -27 3 >> c=[.2 sqrt(5) -2 1.5; -sqrt(3) pi -2.6 14.3; sin(2) -7/2 1 sqrt(2)] c = 1/5 2889/1292 -2 3/2-1351/780 355/113 -13/5 143/10 401/441 -7/2 1 1393/985 . . . . c = 1 2889 -2 3 0 1 -7/10000 11/10000 0 0 1 -9774/19...
View Full Document

{[ snackBarMessage ]}

### Page1 / 5

calc lab 2 - 0 1 5-6 15 3-8 1 0 53>> B(4)=B(4-3*B(1 B =...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online